Metacognitive Strategy Implementation In Teaching English Tenses To College Students: A Classroom Action Research - Gunawan Tambunsaribu (International Journal of Science and Applied Science: Conference Series, 2022)
The purpose of this study is to conduct some steps using a metacognitive strategy for teaching English tenses in order to develop college students’ skills in mastering English writing using three English basic tenses namely simple present tense, simple past tense, and simple future tense. This strategy is considered very effective and implemented by the researcher to increase students’ skills in learning English tenses. This is classroom action research. The students themselves participated in solving their problems related to the materials given based on the syllabus of the English subject. Participants of this research are the students, 33 students, of Gunadarma University who are learning Business English 1 in the academic year of 2020/2021. The result of this study, problem-based learning through some steps using a metacognitive strategy, has been well implemented including the completeness of the lesson plans before teaching each material. Based on the findings, the implementation of a metacognitive learning strategy can improve student achievement by above 100% in mastering English tenses.